Associations of living in residential care facilities with participation in physical activities among older adults in the United States. Issue 1 (1st February 2023) - Zhou, Weijiao; Larson, Janet L.
Abstract: Background: Physical activity (PA) is important for the healthy aging period, and existing research indicates that older adults in residential care facilities (RCFs) are less physically active compared with community-dwelling, but sociodemographic and health-related characteristics were not controlled. Lower PA levels might be due to older age and worse health conditions of the RCFs residents. Objective: This study examined the association between residential status (RCF vs. community-dwelling) and participation in PA, in a sample of 4009 older adults (65 and above) in the National Health and Aging Trends Study (NHATS), adjusting for sociodemographic and health-related characteristics. Methods: The current study used Rounds 8 and 9 of the NHATS which was collected in 2018 and 2019. We conducted design-based logistic regression analyses to determine whether residential care status was significantly associated with participation in walking exercises and vigorous activities, and controlled for sociodemographic and health-related characteristics. Results: Using multivariable logistic regression models, older adults in RCFs (n=214) were more likely to participate in walking exercises (adjusted odds ratios=1.94, P <0.01) and equally likely to participate in vigorous activities (adjusted odds ratios=1.04, P =0.84) than community-dwelling (n=3795). Conclusions: Our finding adds new evidence to the conventional thinking about the potential effect of RCFs on PA. Further research is needed to address the underlying mechanisms.